Solar Pyrolysis of Wood in a Lab-scale Solar Reactor: Influence of Temperature and Sweep Gas Flow Rate on Products Distribution. (May 2015) - Zeng, K.; Flamant, G.; Gauthier, D.; Guillot, E.
Abstract: Experiments of solar pyrolysis of beech wood have been conducted to study the effect of temperature and sweep gas flow rate on the pyrolysis product yields.Investigated variables were pyrolysis temperature, from 600 to 2000 °C, and argon flow rates, between 3Nl/minand 12Nl/min. The heating rate was constant, 50 °C/s. A 50.9 wt.% maximum gas yield(mainly CO and little CH4 ) was obtained at pyrolysis temperature of 2000 °Candargon flow rate of6Nl/min. The gas yield increased with temperature but the trend is not linear. The most important increase of gas yield (from 15.3 wt.% to 37.1 wt.%) anddecrease of liquid yield (from 70.7 wt.% to 51.6 wt.%) were found between 600 and 1000 °C, which meansthat most of tar decomposed in this temperature range. The gas yield decreased when the argon flow rate increased. The two temperature zones of solar reactor were determined by CFD simulation at different sweep gas flow rates.The higher the sweep gas flow rate, the lower the average temperature and the smaller the hot zone in the vicinity of the sample in the solar reactor. This trend is not favorableto the gas formation from tar cracking.